Psychosomatic Primary Care in Gynecology-Assessment and Acceptance by Residents for Obstetrics and Gynecology in Germany - Schott, S.; Lermann, Johannes; Rauchfuss, M.; Ortmann, O.; Ditz, S. (Geburtshilfe und Frauenheilkunde, 2014)
Background: The course "Psychosomatic Primary Care" has been part of the training curriculum of obstetrics and gynecology in Germany since 2003. The aim of the course is to train up physicians, whose prior training primarily focussed on somatic care, to enable them to offer care also taking into account biopsychosocial aspects. Taking the guidelines for psychotherapy as a template, the aim of psychosomatic primary care is to recognize the etiological links between psychological and somatic factors which contribute to diseases. The necessity for a compulsory course as part of training in gynecology was recently critically discussed. Major points discussed included the question whether the current forms of teaching, consisting of courses, are outdated and whether the required skills should be part of regular daily training. Method: A 3-part online questionnaire consisting of 30 items was developed and sent to 2431 residents in the period from September to December 2012 through the online mailing list of the DGGG. Results: The 540 residents who responded to the questionnaire were predominantly female (83.3 %) with an average age of 30 years; 50.3 % were in their 1st to their 4th year of training. Over the longer term, the majority of respondents (56.1 %) hoped to continue working in a hospital and regularly (84.6 %) attended teaching courses voluntarily. 70.9 % of them had already attended the course "Psychosomatic Primary Care". Of the group who had completed the course, 29.4 % were satisfied with the offer. The main criticism directed against the course was its scope which 24.1 % considered completely inadequate. 24.5 % considered the course to be an important part of training, while 16.5 % would have preferred that the course be abolished. 18 % of respondents reported that psychosomatic medicine did not feature regularly in their daily clinical routine. Perspective: Because of the huge gap between what is currently offered and the experiences reported by the respondents, the Young Forum of the DGGG and the DGPFG have expanded the program of courses offered by the DGPFG, which will offer practice-oriented courses to future gynecologists across Germany in cooperation with the DAGG. The first courses are held in Heidelberg and Erlangen in 2014.
EVALuna2:17534